Światy z marzenia : echa romantyczne w poezji Zbigniewa Herberta - Mikołajczak, Małgorzata (1966- ) (Zielona Góra ; Kraków: Wydawnictwo JMR Trans-Atlantyk)
The book discusses the presence of the Romantic tradition in the poetry of Zbigniew Herbert. The very term ?Romanticism? is broadly understood, and encompasses both the characteristics and the attitudes typical of the Romantic period, as well as specific plots and motifs related to particular works. The primary concept of the book consists in the idea that Herbert did not surrender, as it is claimed by Ryszard Przybylski, to "depriving the world of music" and that the Orpheus's lyre was not destroyed.
Keywords: Herbert, Zbigniew (1924-1998) - twórczość; poezja polska - historia - 20 w.